A cross-level diary study of psychological flexibility and its effects on self-esteem and negative emotional dynamics in women survivors of breast cancer - Carmona‐Cobo, I.; Modesta Ballesteros, M.; Camilo, C.; Lima, M. L. (Psycho-Oncology, 2026)
Background Breast cancer primarily affects women from all countries around the world. Psychological flexibility is a personal resource that helps cancer patients accept the disease, reduce emotional distress, and enhance self-esteem. Scarcely explored within this type of breast cancer, it might help women survivors in their daily lives. Aims This study investigates whether trait psychological flexibility in women survivors of breast cancer has benefits for their daytime levels of evening self-esteem, anxiety, and expressive suppression. Methods A total of 94 women (47 breast cancer survivors and 47 controls) completed full diary surveys twice daily for five consecutive workdays (n = 470 daily data). The diary used a two-level design: 5-day repeated measures (Level 1, day-level) nested within persons (Level 2, person-level), employing a within-person approach. Results Multilevel analyses showed main effects of daily morning negative affect on daily evening self-esteem, anxiety, and expressive suppression in the breast cancer group, as well as main effects of trait psychological flexibility on all outcomes for both groups. Cross-level interactions showed that on days when women survivors of breast cancer experienced high levels of daily morning negative affect, those low (vs. high) in trait psychological flexibility decreased their levels of daily evening self-esteem and increased daily evening anxiety and expressive suppression. Conclusions A within-person approach is relevant for understanding psychological flexibility among breast cancer survivors. It has a dual beneficial function for their self-esteem and for negative emotional dynamics daily.